Transcatheter ventricular septal defect closure in infants under 10 kg using only arterial access: a single center experience (Herald of the National Children's Medical Center, 2025)
Aim. Transcatheter closure of ventricular septal defect (VSD) in infants under 10 kg is technically challenging due to small patient size, vascular access limitations, and increased risk of complications. Exclusive arterial access may offer procedural advantages by simplifying the approach. This study evaluates the safety, efficacy, and mid-term outcomes of transcatheter VSD closure using only arterial access in infants under 10 kg.Materials and methods. Twenty infants (9 males [45%], 11 females [55%]) with a median age of 14.5 months (IQR 10–21.5) and median weight of 8.95 kg (IQR 8–9) underwent transcatheter VSD closure via arterial access alone. Median VSD size was 4.5 mm (IQR 3.5–4.95), and device diameter ranged from 7×5 to 8×6 mm (median 7×5). Median fluoroscopy dose was 19 mGr (IQR 13–29.5), and median procedure time was 50 minutes (IQR 40–60). The median follow-up duration was 15 months (IQR 12–22).Results. Procedural success was 100%. Residual shunt at 1 year was observed in 15% of patients. Tricuspid regurgitation occurred in 30%, with no aortic regurgitation reported. No major complications or mortality were documented.Conclusion. Transcatheter VSD closure in infants under 10 kg using only arterial access is a feasible and safe approach with favorable mid-term outcomes. This technique may reduce procedure time and contrast load, making it an attractive option for small infants.
Keywords: ventricular septal defect; konar; infant